All Days 1998
DOI: 10.2118/47380-ms
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Hydraulic Fracture Closure in Laboratory Experiments

Abstract: CC?Yrwht 1S9S, S@Iely of Pelroteum Engrneem, IncThis paper was prepared for pmsantation qt the SPE/lSRM Eurcck '9S held In TrwMhelm, Norway, S-10 Jufy 1S9S, This paper Ws selected for pree.wltdicm by an SPE Program Ccinmittae Iotlowfng review of infonnatmm cc+xained in an abstmcf sutmitfod by the author(s). CcmIents of the paper, as presented, have not been rwiewed by the Sceiety of Petroleum Engineers and we sub~to mrrectm by the Mhor(s), The nwlerml, as presented, daes not necassanty reflecl any Pition of Ih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…When we incorporated the measured radius in plaster in the model and assumed that the closed part of the fracture was impermeable, we indeed found a fair agreement of the modeled fracture volume with the measured volume. 5 Closure at the borehole can be detected directly from the width measurement. The closure point is clearly visible on a plot of pressure vs. G-function (see Fig.…”
Section: Fracture Closurementioning
confidence: 99%
“…When we incorporated the measured radius in plaster in the model and assumed that the closed part of the fracture was impermeable, we indeed found a fair agreement of the modeled fracture volume with the measured volume. 5 Closure at the borehole can be detected directly from the width measurement. The closure point is clearly visible on a plot of pressure vs. G-function (see Fig.…”
Section: Fracture Closurementioning
confidence: 99%
“…Fracture surface roughness in combination with a small displacement of opposing fracture surfaces relative to each other, causes imperfect closing due to the non-matching surfaces. This leads to a residual width after closure, which is observed in laboratory tests 1 , and also in field tests 2 . The residual width leads to a fracture conductivity after closure, which can be so large that proppant volumes can be reduced strongly or even can be omitted 3 .…”
Section: Introductionmentioning
confidence: 59%
“…Fracture roughness can also cause problems with proppant transport. Further, the presence of a significant residual width influences the wellbore pressure during reopening of a hydraulic fracture 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laboratory experiments indicated that the fracture will gradually close with pressure drop within the fracture 12 and the permeability of the fracture will also decay with effective stress increase during a reduction of fracture pore pressure caused by production 13 . During the flowback period, there are many researches 6,7 found that the parameters of the fracture calculated by two‐phase flow data after hydrocarbon breakthrough are less than that calculated by single‐phase flow data before hydrocarbon breakthrough.…”
Section: Introductionmentioning
confidence: 99%